IDENTIFIKASI SEKTOR UNGGULANDALAM PEREKONOMIAN SUMATERA UTARA - Sri Winda Hardiyanti Damanik (Universitas Negeri Medan, 2018)
Identification process u Sectors in an area must be carried out to develop economic development planning. This study discusses changes and changes in the economic sector in North Sumatra Province and the causal relationship between sectors in the economy in North Sumatra Province. Research Objectives To understand and analyze changes and distribution of the North Sumatra sector and analyze the relationships between sectors in the economy in North Sumatra Province. The method used in this study is shift share analysis and estimation with the Granger Causality. By using shift share analysis in aggregate, there is an increase in the level of economic output during 2011 - 2015 and largely due to economic growth at the national level, while affecting the effects of the industrial / sectoral mix (proportionate part) on North Sumatra's economic growth which has a negative impact . estimation results with the Granger Causality note that the sector and tertiary sectors affect the primary sector, the tertiary sector affects the secondary sector and is not related to the causality relationship between the primary sector, the secondary sector and the tertiary sector